Evaluation of utilization of amplified blastocoel fluid DNA gel electrophoresis band intensity as an additional minimally invasive approach in embryo selection: A cross-sectional study - Fattaneh Khajehoseini; Zahra Noormohammadi; Poopak Eftekhari-Yazdi; Hamid Gourabi; Reza Pazhoomand; Shirzad Hosseinishenatal; Masood Bazrgar (International Journal of Reproductive BioMedicine)
Background: Embryo selection for transfer is critical in assisted reproduction. The presence of DNA in the blastocoel cavity of human blastocysts is assumed to be a consequence of common preimplantation chromosomal abnormalities.